Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Kerjasama Tim terhadap Kinerja Karyawan pada Jakarta Convention Center - Allisya Andrea Anjani (Journal Economic Excellence Ibnu Sina, 2024)
The work environment, discipline and teamwork of a company greatly determines the company's performance, as does the Jakarta Convention Center where human resources have a very big role because it is humans who carry out activities within the company so that the company is able to achieve its goals. This research aims to test and analyze the influence of the work environment, work discipline, and teamwork on employee performance at the Jakarta Convention Center. Respondents in this research were employees of the Jakarta Convention Center. Based on random sampling techniques, the type of sample used in the research was saturated sampling so that the respondents in this study were all 150 employees of the Jakarta Convention Center. This research uses primary data obtained from distributing questionnaires. The analytical method used in this research is multiple linear regression analysis. The research results show that simultaneously or partially, work environment variables, work discipline and teamwork have a positive effect on the performance variables of Jakarta Convention Center employees.